FAKTOR PENYEBAB RENDAHNYA PRESTASI BELAJAR PESERTA DIDIK DAN PELAYANAN GURU BK - Sativa, Oriza - (Bimbingan dan Konseling, 2014)
Background of this research was low studentâs result of study at SMK Negeri 4 Padang. The purpose of this research to describe internal and external factor which cause low studentâs achievement and treatment do by counselor. Design of this research is descriptive research. Moreover, the informants in this research are 3 low achiever students, 3 counselors and 3 friends of the students. To collect the data, the researcher use interview and documentation. Furthermore, the reseacher analyze the data through data reduction, presenting of the data and making conclusion. The result of this reaserch shows internal factors which cause low studentâs achievement in learning are condition of the school is not good, the subject is taken by the studens is not appropriate with their competence and what their want. In addition, external factors which cause low studentâs achievement are studentâs rare socialize with their friends, their teachers, staff in the school environment and less learning facility, and service counselor to the factors causing low academic achievement of students is changing habits and motivate learners to become better.